2019
DOI: 10.1039/c9ra02042j
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Thymus vulgaris aqueous extract to protect against delayed gastric emptying and colonic constipation in rats

Abstract: Thyme is a rich source of bioactive phytochemicals and it is frequently used in folk-medicine to treat gastroenteritis irritations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…Our results revealed that thyme composition comprises phenolic components including gallic acid, 4-amino benzoic acid, protocatchuic acid, chlorogenic acid, catechol, vanillic acid, p-coumaric acid, isoferulic acid, αcoumaric acid, 3, 4, 5 methoxycinammic, coumarin, and cinammic acid with concentration ranging from 10 to 100 ppm. This is consistent with the findings of Varga et al [40], Köksal et al [41], El-Newary et al [42], and Rtibi et al [43] who reported that typical thyme constituents included pyrogallol, caffic acid, ferulic acid, and benzoic acid. Furthermore, thyme __________________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Determination Of Phenolic and Flavonoid Components Of Dry Thyme Powdersupporting
confidence: 92%
See 1 more Smart Citation
“…Our results revealed that thyme composition comprises phenolic components including gallic acid, 4-amino benzoic acid, protocatchuic acid, chlorogenic acid, catechol, vanillic acid, p-coumaric acid, isoferulic acid, αcoumaric acid, 3, 4, 5 methoxycinammic, coumarin, and cinammic acid with concentration ranging from 10 to 100 ppm. This is consistent with the findings of Varga et al [40], Köksal et al [41], El-Newary et al [42], and Rtibi et al [43] who reported that typical thyme constituents included pyrogallol, caffic acid, ferulic acid, and benzoic acid. Furthermore, thyme __________________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Determination Of Phenolic and Flavonoid Components Of Dry Thyme Powdersupporting
confidence: 92%
“…63, No. 11 (2020) composition includes high concentration of some other compounds such as catechin, caffeine, p-OH benzoic, ellagic acid, and salicylic acid [42,43,44]. Meanwhile, hesperidin was high concentration in flavonoid.…”
Section: Determination Of Phenolic and Flavonoid Components Of Dry Thyme Powdermentioning
confidence: 99%
“…Among the 12 components, protocatechuic acid, chlorogenic acid, rutin and isoquercetin showed promising pharmacological activities in constipation (Rtibi et al. 2019 ), smooth muscle-relaxing (Tóth et al. 2015 ) and anti-inflammatory (Ezenyi et al.…”
Section: Discussionmentioning
confidence: 99%
“…For Thymus species, multiple studies have been conducted using mostly ethanol, methanol, water, and their mixture as solvents, in which not much variety was observed in the flavones extraction of such species as T. alternans, T. caespititius, T. fragrantissimus, T. mastichina, T. pulegioides, T. serpyllum, and T. vulgaris, among others [68,71,[117][118][119][120][121]. However, using fractionation techniques, it is possible to obtain flavones that have not been identified in crude extracts such as 7-methoxyapigenin (genkwanin) [122] and nobiletin [123,124], while, by using dichloromethane, hydroxyluteolin and hydroxyapigenin derivatives can be extracted from T. mastichina [125].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%